Psychiatry postgraduate training in Malaysia : training curriculum - Zainal, Nor Zuraida; Gill, Jesjeet Singh; Mohd Yasin, Mohd Azhar; Husain, Maruzairi; Baharuddin, Azlin; Nik Jaafar, Nik Ruzyanei; Ibrahim, Normala; Ohnmar Naing, Noorjan @ Khin; Kiat, Ang Jin; Hamdie Yusoff, Eizwan; Razali, Salmi; Mat Zin, Nora Mat Zin (Majlis Dekan Fakulti Perubatan Universiti Awam Malaysia MERDU, Fakulti Perubatan, Universiti Malaya, 50603 Kuala Lumpur, Malaysia npmcmy@gmail.com, 2021)
This document is one of a number of specialty modules that form the Malaysian National Postgraduate Medical curriculum. It represents the collaboration between the Malaysian Public Universities and the Ministry of Health (MOH) to provide a single, agreed programme for the training of psychiatrists throughout the country. Universities and Ministry of Health programmes may utilise the different pathways specified in this curriculum. Whilst individual universities and the MOH may adopt different approaches for the delivery of training, it is expected that the curriculum contents will broadly guide the requirements for the Knowledge, Skills and Behaviours not just in clinical practice, but also in training, research and management. The curriculum has been designed to document and describe the knowledge, clinical skills, soft skills and attitudes required to practice psychiatry. This document constitutes the ONE curriculum for ALL and the authors have committed to provide a thoroughly discussed and agreed set of guidelines which, if followed, will ensure the most effective use of resources and a uniformly high standard of clinical practice in Malaysian Psychiatry. Writers The process of developing the National Postgraduate Psychiatry Curriculum involved numerous authors and contributors who were appointed and supported by the Psychiatry Specialty Committee.